A Study on Saint Meira: Syncretism and Oral Tradition in Madhesh, Nepal (NPRC Journal of Multidisciplinary Research, 2025)
This study explores the tradition of Saint Meira (also known as Meeran Saheb or Meera Baba), a syncretic folk saint venerated by both Hindus and Muslims in the Madhesh region of Nepal. Grounded in the frameworks of religious syncretism, cultural hybridity, and interpretive anthropology, the research investigates how the veneration of Saint Meira operates as a form of interfaith devotional culture rooted in oral tradition and communal memory. Drawing from fieldwork in the Dhanusha, Siraha, Mahottari and Rautahat districts—including oral history interviews, ethnographic observations, and analysis of folklore—the study documents the narratives, rituals, and symbolic meanings associated with the saint. The findings demonstrate that Meira’s worship serves as a unifying cultural practice that transcends religious boundaries and strengthens communal identity in a diverse society. The study also critically examines the purported connection between Saint Meira and the legendary folk hero Karikh Maharaj, concluding that their association reflects dynamic processes of folk myth-making rather than historical continuity. While the tradition remains a vital expression of grassroots pluralism, it faces challenges from increasing religious orthodoxy and generational shifts. This research contributes to the broader discourse on religious syncretism in South Asia and highlights the need for preserving indigenous interfaith traditions in rapidly transforming cultural landscapes.